2007
DOI: 10.1021/bi7010948
|View full text |Cite
|
Sign up to set email alerts
|

IIAGlc Inhibition of Glycerol Kinase:  A Communications Network Tunes Protein Motions at the Allosteric Site

Abstract: Steady-state and time-resolved fluorescence anisotropy methods applied to an extrinsic fluorophore that is conjugated to non-native cysteine residues demonstrate that amino acids in an allosteric communication network within a protein subunit tune protein backbone motions at a distal site to enable allosteric binding and inhibition. The unphosphorylated form of the phosphocarrier protein IIAGlc is an allosteric inhibitor of Escherichia coli glycerol kinase, binding more than 25 A from the kinase active site. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…EGK and A65T EGK were purified as described [33, 34]. The plasmid construct for the R369A EGK was generously supplied by Dr. S. James Remington of the University of Oregon.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…EGK and A65T EGK were purified as described [33, 34]. The plasmid construct for the R369A EGK was generously supplied by Dr. S. James Remington of the University of Oregon.…”
Section: Methodsmentioning
confidence: 99%
“…The R369A EGK enzyme was purified as described [33]. The site-directed variant EGK enzymes E92C and E121C were constructed as described [34]. These enzymes were purified by using Q-Sepharose HP, Source 15Q, and ATP-agarose (C-8 linkage) affinity chromatographies on an Akta Purifier system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approaches for identification of these networks include bioinformatics methods [7, 9, 10], computational methods [2, 4, 11-13], and structure-based experimental methods [5, 14-18]. We used an approach that is based on transplanting allosteric control into a naïve enzyme to identify a locus that is part of an allosteric network [19] and showed that the locus modulates local motions and binding affinity at the allosteric site [20]. Here, we evaluate the role of this locus in the coupling between the allosteric and catalytic sites.…”
mentioning
confidence: 99%